Análise e levantamento das manifestações patológicas através de mapa de danos, em prédios históricos do estado de Pernambuco, devido a falta de manutenção e recuperação. - Borba, Lucas Feliciano Ferreira (2022)
Today, there is a focus on the quality and performance of buildings. Durability and longevity of construction materials are concepts that were not evaluated in buildings before and today are fundamental to the decisions of design and execution of buildings. The city of Recife has a great variety of historical monuments that present many pathological manifestations that degrade the structure, reduce its useful life and put at risk the stability of our precious patrimony. In view of this, there are concerns about the correction of these pathological manifestations and the preservation of this heritage. Studying the pathological manifestations of historic buildings becomes fundamental, because this is the way to understand the mechanisms that degenerate them. The lack of maintenance favors this problem, as it can lead to the development and dissemination of anomalies, increasingly reducing the service life of the structure. The study was developed with the purpose of stimulating the valorization of Pernambuco's heritage riches. For this, 03 buildings of the city were chosen, namely, the São José Church of the extinct São José retreat house, the Museum of Archeology and Natural Sciences, and the Nossa Senhora de Fátima Church. These were selected according to the following criteria: listing by the Institute for National Historic and Artistic Heritage - IPHAN; social importance; accessibility; and availability of data. This study aims to evaluate the conservation status of the facades of buildings located in the city of Recife and Olinda in order to contribute to the restoration and/or conservation of the selected buildings. The methodology used in the research began with a literature review, followed by the selection of the buildings with the application of a check-list, which allows the elaboration of a data identification sheet, photographic record, and verification of the lack of maintenance, essential tools for the composition of the Damage Map of the studied facades. With the data collected, the information was compiled and the damage maps of the buildings studied were composed, and the most recurrent manifestations on the facades of the buildings studied were dirtiness/black crust and paint detachment. The study of the pathology of the buildings and the use of Damage Maps are fundamental tools for the treatment and preservation of historic buildings. The material produced facilitates the execution of future restorations, besides promoting and valuing the historic heritage of Recife.